Smart Village Governance: Citizen Participation In Panggungharjo Village-Owned Enterprise - Dyah Mutiarin; Muhammad Iqbal (Universitas Muhammadiyah Gorontalo, 2021)
This study focuses on participation in the implementation and influence of community participation on the application of Smart Village in Village-Owned Enterprise. In the theory of community participation in the implementation phase, there are indicators to measure community participation, namely participation with energy, participation with money, participation with goods, and also participation with ideas. This research uses a quantitative approach with data collection, namely questionnaires and literature study. The population number of studies was 28141 people. The sample calculation results in this study were 100 respondents. The survey results are then processed using SmartPLS 3.0 software. The results show that of the four indicators of community participation mentioned above, two of them influence the development of Smart Village. At the same time, the other two do not affect the development of Smart Village. Indicators that influence the development of Smart Village are participation with energy and participation with goods. In other words, residents of Panggungharjo Village participated in the implementation of the Smart Village in Village-Owned Enterprise and donated some of the items needed to develop the Sustainable Village-Owned Enterprise Panggung Lestari. Whereas participation with money and participation with ideas do not influence the development of Smart Village. The recommendation in this study is that the village government or Village-Owned Enterprise managers can increase community participation in various ways such as involving the community directly in the management of Village-Owned Enterprise and providing space for the community to contribute actively to the form of physical participation